Effect of high-fidelity shoulder dystocia simulation on emergency obstetric skills and crew resource management skills among residents. Issue 3 (December 2016) - Mannella, Paolo; Palla, Giulia; Cuttano, Armando; Boldrini, Antonio; Simoncini, Tommaso
Abstract: Objective: To determine the effect of a simulation training program for residents in obstetrics and gynecology in terms of technical and nontechnical skills for the management of shoulder dystocia. Methods: A prospective study was performed at a center in Italy in April–May 2015. Thirty-two obstetrics and gynecology residents were divided into two groups. Residents in the control group were immediately exposed to an emergency shoulder dystocia scenario, whereas those in the simulation group completed a 2-hour training session with the simulator before being exposed to the scenario. After 8 weeks, the residents were again exposed to the shoulder dystocia scenario and reassessed. Participants were scored on their demonstration of technical and nontechnical skills. Results: In the first set of scenarios, the mean score was higher in the simulation group than the control group in terms of both technical skills ( P = 0.008) and nontechnical skills ( P < 0.001). This difference was retained after 8 weeks. Conclusion: High-fidelity simulation programs could be used for the training of residents in obstetrics and gynecology to diagnose and manage obstetric emergencies such as shoulder dystocia.